A meta-diisocyanide benzene-based aryl gold isocyanide complex exhibiting multiple solid-state molecular arrangements and luminescent mechanochromism. (4th May 2018) - Seki, Tomohiro; Ida, Kentaro; Ito, Hajime
Abstract : A meta -disubstituted aryl gold isocyanide complex showing pseudopolymorphism exhibit various emission properties. These pseudopolymorphs also show reversible luminescent mechanochromism. Abstract : Functional organic solids with switchable photoluminescence properties in response to external stimulation have attracted much interest because of their potential applications in sensors and imaging devices. Among these organic solids, luminescent mechanochromic compounds are emerging materials that can switch their photoluminescence properties when mechanically perturbed. Our group has intensively studied the solid-state emission properties and luminescent mechanochromism of a series of aryl gold isocyanide complexes. Here, we prepared bent-shaped binuclear gold isocyanide complex2, which exhibits different pseudopolymorphs with different emission properties when prepared using different crystallization procedures. X-ray diffraction measurements and NMR spectroscopy indentified inclusion of solvent molecules in the crystalline lattices of2 except for one polymorph. Complex2 also shows luminescent mechanochromism based on a crystalline-to-amorphous phase transition. The ground phases of all of the pseudopolymorphs revert to the polymorph without solvent molecules upon thermal treatment.